Sir Moses Montefiore (1784-1885), défenseur de la foi - Suzy Halimi (Revue Française de Civilisation Britannique)
Sir Moses Montefiore is hardly to be found in the books of the historians of Victorian Britain. He was however an important figure of the time, a friend of many important personalities in the political, social and religious circles. An orthodox Jew, he strictly observed the dictates of his faith in his daily life and especially that basic law of Judaism, the practice of charity. A very rich man, he used his money for the relief of the poor, without any distinction of religion, supporting, for instance, the great philanthropist, Lord Shaftesbury, in the development of education for destitute children. His action also reached beyond the seas, when he flew to the rescue of his co-religionists persecuted in several parts of the world. Supported by his Government, he thus became the mouthpiece of tolerance, of the rights of man and of the values of British civilization.When the question of Jewish Emancipation was hotly discussed in Parliament, he supported the movement as President of the British Board of Deputies, fearing at the same time that the conquest of civil rights might encroach upon a strict observance of his faith. And when the traditional orthodoxy was questioned by a number of Jews, eager to ‘modernize’ the practice of Judaism in order to promote Emancipation, then he was deadly against those ‘heretics’ and strongly opposed their admission to the Board as long as he remained its President.